(untitled) (American Journal of Islam and Society, 1988)
Introduction Some idea of the past is present in every culture, and historical consciousness as an awareness of this past is a distinctive element in total cultural expression. Hence, it would be a mistake to assume that there was no historical consciousness among the Arabs predating Islam. However, it was the religious, political and social transformation of the Arabs through Islam that motivated an extensive interest in the past and its systematic recording. Muslim historians developed the idea of the past they had inherited from pre-Islamic Arabia and expressed it in an extensive historical literature. The study of the past in early Islamic history was motivated and determined by a number of factors. This article seeks to outline some of the important developments which led to a distinctive Islamic historiography. It seeks to do so by an examination of studies conducted on the early Islamic historical tradition. In particular, three fundamental aspects of the different phases of historical writings from pre-Islamic Arabia through the 2nd and 3rd centuries of the Hijrah are investigated: the external form of historical recollection; its subject matter; and the meaning and significance of both the form and the subject matter of historical recollection in the culture. 1. Pre-Islamic Arabia The interest in the past among the pre-Islamic Arabs is best exemplified by the custom of evening tribal gatherings, called majalis, at which the special ...